2015
DOI: 10.1007/s13277-015-4038-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 suppressed the growth of lung carcinoma by reducing MEF2D expression

Abstract: Lung carcinoma is a deadly malignant disease with poor prognosis and increasing incidence in recent years. However, the molecular mechanism underlying the initiation and progression of lung cancer is still not completely elucidated. Recently, myocyte enhancer factor 2D (MEF2D) has been reported to promote the growth of liver cancer, but its implication in lung cancer is still unknown. This study is aimed to determine the role of MEF2D in lung carcinoma. Quantitative PCR (qPCR) and immunoblot assays showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Therefore, it was hypothesized that the suppression of MEF2D was responsible, at least in part, for the antitumor effect of miR-30a. In accordance, Song et al (24) demonstrated that the expression of MEF2D is decreased by another miR (miR-218), in lung carcinoma. One possible explanation is that the same miR may have different targets and the same mRNA may be targeted by different miRs in diverse cell types (22,24).…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, it was hypothesized that the suppression of MEF2D was responsible, at least in part, for the antitumor effect of miR-30a. In accordance, Song et al (24) demonstrated that the expression of MEF2D is decreased by another miR (miR-218), in lung carcinoma. One possible explanation is that the same miR may have different targets and the same mRNA may be targeted by different miRs in diverse cell types (22,24).…”
Section: Discussionsupporting
confidence: 61%
“…Altered MEF2 activity serves a role in human diseases and it has recently been implicated in the initiation and progression of various types of cancer in humans (31). Recently, it was reported that MEF2D, one member of MEF2 family, is involved in the progression of several cancer types, including lung carcinoma (27), rhabdomyosarcoma (32), hepatocellular carcinoma (31) and osteosarcoma (25).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA target prediction websites www.microRNA.org and TargetScan (www .targetscan.org) were used to predict the target gene of miR-30a. The 3'-UTR of MEF2D containing the putative binding site of miR-30a was amplified and subcloned into a pGL3 luciferase promoter vector (Promega Corporation, Madison, WI, USA), as described previously (27); the putative binding site was mutated as negative control (MEF2D-Mut). The vector was co-transfected with miR-30a mimic into 293 cells for 48 h. The cells were harvested and relative luciferase activity was detected using a Dual-Luciferase Reporter Assay System (Promega Corporation) according to the manufacturer's protocol.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Notably, for the first time, we established the link between miR-1244 expression and cisplatin-treated NSCLC cell growth. MEF2D, a member of the myocyte enhancer factor 2 family of transcription factors, has been shown to be expressed in NSCLC cells and to increase the proliferation rate of cells by increasing G2/M transition (14). MEF2D is a target of miR-122 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Its main function is to regulate the survival and differentiation of multiple cell types. Early studies on MEF2 were predominantly limited to its role in muscle and the nervous system (14). However, numerous studies have demonstrated that chromosome translocation in NSCLC may result in abnormally high expression of MEF2D and promote the formation and development of NSCLC (15).…”
Section: Introductionmentioning
confidence: 99%